Genetics of age-related clonal hematopoiesis and atherosclerotic cardiovascular disease. (May 2020) - Jung, Changhee; Evans, Megan A.; Walsh, Kenneth
Abstract : Purpose of review: While advanced age is the major risk factor for the development of atherosclerotic cardiovascular disease (ASCVD), we have a poor understanding of how aging promotes the progression of this disease. Recent evidence suggests that the age-dependent accumulation of somatic mutations in hematopoietic cells may represent a new causal risk factor for ASCVD. Recent findings: A hallmark of aging is the accumulation of somatic DNA mutations in all tissues of the body. Accordingly, evidence shows that hematopoietic stem/progenitor cells accumulate somatic mutations as a function of age in nonsymptomatic individuals. When these mutations occur in driver genes that provide a selective advantage to the hematopoietic stem/progenitor cells, they undergo a clonal expansion and progressively give rise to blood leukocytes that harbor these mutations. This phenomenon, referred to as clonal hematopoiesis, has been associated with the increased risk of mortality, hematologic malignancy, ASCVD, and related diseases. Notably, many individuals exhibiting clonal hematopoiesis carry single 'driver' mutations in preleukemic genes including DNA methyltransferase 3a, ten-eleven translocation 2, additional sex combs like 1, and Janus kinase 2 . Experimental studies show that these mutations in some of these genes can alter the inflammatory properties of the leukocyte and contribute to the pathogenesis of ASCVD. Summary: We review recent epidemiological and experimental findings on the association between age-related clonal hematopoiesis and ASCVD by focusing on prevalent driver gene mutations.